Something is killing the children. Volume two - Tynion, James, IV (BOOM! Studios, 2020)
"EVIL NEVER DIES...UNLESS ERICA SLAUGHTER KILLS IT. Erica Slaughter may have slain the monster terrorizing the small Wisconsin town of Archer's Peak, but the horror is far from over. As her mysterious handler arrives in town to clean up her mess and quarantine the townsfolk, Erica sets off deeper into the woods -- because the monster she killed was a mother... and now she needs to kill its children."--Provided by publisher.